Production of syrup rich in arabinoxylan oligomers and antioxidants from wheat bran by alkaline pretreatment and enzymatic hydrolysis, and applicability in baking. (September 2020) - Pihlajaniemi, Ville; Mattila, Outi; Koitto, Taru; Nikinmaa, Markus; Heiniö, Raija-Liisa; Sorsamäki, Lotta; Siika-aho, Matti; Nordlund, Emilia
Abstract: The target of this work was to develop a novel, industrially applicable process for simultaneously releasing different valuable components from wheat bran, including carbohydrates, oligomeric arabinoxylan and antioxidants. The process was based on alkaline pretreatment with potassium hydroxide (KOH) and subsequent enzymatic hydrolysis. Increasing KOH-dosage and thermal severity in pretreatment promoted carbohydrate solubilisation in hydrolysis, reaching glucose and arabinoxylan yields up to 86% and 76%, respectively. Release of antioxidants was particularly promoted by increasing KOH-dosage, while both the pretreatment severity and KOH-dosage promoted the release of oligomeric arabinoxylan in enzymatic hydrolysis. Two bran syrups, with or without KOH-treatment, were tested in bread making by substituting added sugar in the dough with bran syrup. The KOH-derived KCl also substituted 30% of NaCl in the bread formulation. The addition of bran syrup did not affect the baking properties of wheat bread dough. However, a decrease in bread flavour balance was observed with addition of syrup from KOH-pretreated bran. Conceptual level techno-economic assessment indicated that production of bran syrup would be economically feasible at a minimum selling price of 770 €/t and 1030 €/t with KOH-pretreatment and without KOH, respectively. Graphical abstract: Image 1 Highlights: KOH-pretreatment and enzymatic hydrolysis released up to 82% of bran carbohydrates. Antioxidant and oligosaccharide release correlated with KOH-loading. Effect of bran syrup on the sensory quality of bread depended on KOH-treatment. The KOH in pretreatment could be completely utilized in the product.